Inherited Metabolic Diseases A Clinical Approach - Hoffmann, Georg F.; Zschocke, Johannes; Nyhan, William L. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The explosion of insights in the field of metabolic disease has shed new light on diagnostic as well as treatment options.  'Inherited Metabolic Disease - A Clinical Approach' is written with a reader-friendly consistent structure. It helps the reader to find the information in an easily accessible and rapid way when needed. Starting with an overview of the major groups of metabolic disorders it includes algorithms with questions and answers as well as numerous graphs, metabolic pathways, and an expanded index. Clinical and diagnostic details with a system and symptom based are given to facilitate an efficient and yet complete diagnostic work-up of individual patients. Further, it offers helpful advice for emergency situations, such as hypoglycemia, hyperammonemia, lactic acidosis or acute encephalopathy. Five different indices allow a quick but complete orientation for common important constellations. Last but not least, it has an appendix with a guide to rapid differential diagnosis of signs and symptoms and when not to suspect metabolic disease. It will help physicians to diagnose patients they may otherwise fail to diagnose and to reduce unnecessary referrals. For metabolic and genetic specialists especially the indices will be helpful as a quick look when being called for advice. It has all it needs to become a gold standard defining the clinical practice in this field.